Reactivation of Fault Systems by Compartmentalized Hydrothermal Fluids in the Southern Andes Revealed by Magnetotelluric and Seismic Data. Issue 12 (25th November 2020) - Pearce, R. K.; Sánchez de la Muela, A.; Moorkamp, M.; Hammond, J. O. S.; Mitchell, T. M.; Cembrano, J.; Araya Vargas, J.; Meredith, P. G.; Iturrieta, P.; Pérez‐Estay, N.; Marshall, N. R.; Smith, J.; et al.
Abstract: In active volcanic arcs such as the Andean volcanic mountain belt, magmatically sourced fluids are channeled through the brittle crust by faults and fracture networks. In the Andes, volcanoes, geothermal springs, and major mineral deposits have a spatial and genetic relationship with NNE trending, margin‐parallel faults and margin‐oblique, NW trending Andean Transverse Faults (ATF). The Tinguiririca and Planchón‐Peteroa volcanoes in the Andean Southern Volcanic Zone (SVZ) demonstrate this relationship, as their spatially associated thermal springs show strike alignment to the NNE oriented El Fierro Thrust Fault System. We constrain the fault system architecture and its interaction with volcanically sourced hydrothermal fluids using a combined magnetotelluric (MT) and seismic survey that was deployed for 20 months. High‐conductivity zones are located along the axis of the active volcanic chain, delineating fluids and/or melt. A distinct WNW trending cluster of seismicity correlates with resistivity contrasts, considered to be a reactivated ATF. Seismicity occurs below 4 km, suggesting activity is limited to basement rocks, and the cessation of seismicity at 9 km delineates the local brittle‐ductile transition. As seismicity is not seen west of the El Fierro fault, we hypothesize that this structure plays a key role in compartmentalizing magmatically derived hydrothermal fluids to the east, where the fault zone acts as a barrier to cross‐fault fluid migration and channels fault‐parallel fluid flow to the surface from depth. Increases in fluid pressure above hydrostatic may facilitate reactivation. This site‐specific case study provides the first three‐dimensional seismic and MT observations of the mechanics behind the reactivation of an ATF. Key Points: In the Andean volcanic arc, margin‐parallel and blind oblique fault systems control volcanic, hydrothermal, and ore‐porphyry processes Subsurface conductivity structure and seismicity show a WNW trending active fault in the Andean Southern Volcanic Zone Results show magmatic/hydrothermal fluids are compartmentalized by local faults and elevated fluid pressures promote fault reactivation